Analysis of unplanned revisits and readmissions: results of the General Surgery clinic in a private hospital - Narmanlı, Mustafa; Özgüç, Halil; Çevikkalp, Eralp; Serbest, Nesrin (The European Research Journal, 2022)
Objectives: In recent years, the rate of readmission (RA) within the first thirty days of discharge has been an important parameter for cost and quality standards. It is therefore extremely important for each center to analyze its own results and determine the factors affecting the RA rates in order to organize the measures to be taken. Another important issue, especially for centers focusing on specific areas of expertise, is unplanned revisit (RV) after discharge. Determination of these rates and reasons is of importance for every hospital and/or clinic to decrease these rates, thus increasing patient satisfaction and reducing costs. The aim of this study was to analyze RA and RV patients operated in the general surgery clinic of our hospital for a period of two years as well as factors affecting these rates. Methods: The study included patients who were operated in the general surgery clinic of Bursa Private Medicabil Hospital between 1 January 2018 and 31 December 2019 and who revisited and were readmitted within the first thirty days of discharge. The reasons for RA/RV and time to RA/RV, and patients’ treatments were investigated by comparing RA/RV patients with those who were not readmitted (NA) for demographic results at initial admission to determine the differences between these patient groups. Univariate and multivariate analyses were carried out using the SPSS software. The level of significance was set at p < 0.05. Results: Of the 890 patients who were operated in our clinic throughout the study period and met the study inclusion criteria, 52 (5.8%) were included in the unplanned RA group and 107 (12%) in the unplanned RV group. The mean time to RA was 10.5 ± 7.0 days for the RV group and 8.8 ± 6.7 days for the RA group (p = 0.17). Thirty-two (61.5%) of the RA patients and 41 (38.3%) of the RV patients were readmitted within the first 7 days of discharge (p = 0.003). The multivariate analysis revealed that prolonged length of hospital stay, emergency surgery, abnormal WBC, electrolyte imbalance, and abnormal hemoglobin level were significant risk factors for RV, while the development of complications, prolonged length of hospital stay, and advanced age were significant risk factors for RA. Conclusions: This study analyzing the RA and RV patients operated in the general surgery clinic of a private hospital demonstrated that the most important reasons for RA were nonspecific and preventable. Patients who developed complications, had prolonged length of hospital stay, and were at an advanced age had a higher rate of RA, while patients who had prolonged length of hospital stay, underwent emergency surgery, and had biochemical problems at initial admission had a higher rate of RV. Focusing on these patients during and after discharge and increasing home care facilities can solve the problems of many patients without admitting them to the hospital. This will be a factor that would improve patient satisfaction while reducing costs.